Sixteen novel mutations in PNPLA1 in patients with autosomal recessive congenital ichthyosis reveal the importance of an extended patatin domain in PNPLA1 that is essential for proper human skin barrier function. (1st August 2017) - Zimmer, A.D.; Kim, G.J.; Hotz, A.; Bourrat, E.; Hausser, I.; Has, C.; Oji, V.; Stieler, K.; Vahlquist, A.; Kunde, V.; Weber, B.; Radner, F.P.W.; et al.
Summary: Background: Autosomal recessive congenital ichthyosis (ARCI) is a genetically heterogeneous group of rare Mendelian skin disorders characterized by cornification and differentiation defects of keratinocytes. Mutations in nine genes including PNPLA1 are known to cause nonsyndromic forms of ARCI. To date, only 10 distinct pathogenic mutations in PNPLA1 have been reported. Objectives: To identify new causative PNPLA1 mutations. Methods: We screened genetically unresolved cases, including our ARCI collection, comprising more than 700 families. Screening for mutations was performed either by direct Sanger sequencing or in combination with a multigene panel, followed by sequence and mutation analysis. Results: Here we report on 16 novel mutations present in patients from 17 families. While all previously reported mutations and most of our novel mutations are located within the core patatin domain, we report five novel PNPLA1 mutations that are downstream of this domain. Thus, as recently described for PNPLA2, we hypothesize that a region larger than the core domain is required for full enzymatic activity of PNPLA1 in human skin barrier formation. Conclusions: We estimate the frequency of PNPLA1 mutations among patients with ARCI to be around 3%. Most of our patients were born as collodion babies and showed a relatively mild ichthyosis phenotype. In four unrelated patients we observed a cyclic scaling course, which seems to be a potential phenotypic variation in a small percentage of patients with PNPLA1 mutations. The variability of the clinical manifestations and the lack of typical clinical features are specific for patients with PNPLA1 mutations, and emphasize the importance of DNA sequencing for differential diagnosis of ARCIs.